1970
DOI: 10.32734/jpt.v3i3.2987
|View full text |Cite
|
Sign up to set email alerts
|

Pemanfaatan Lahan Gambut Untuk Perkebunan Kelapa Sawit Di Areal Hutan Rawa Gambut Tripa Provinsi Aceh : Kendala Dan Solusi

Abstract: ABSTRAKAreal Hutan Rawa Gambut Tripa (TPSF) Provinsi Aceh dengan luas areal 60.657,29 ha sebagian besar merupakan tanah gambut dengan ketebalan bervariasi dari 100 cm hingga >850 cm. Lebih dari 80% areal TPSF telah dimanfaatkan untuk perkebunan kelapa sawit dan kebun campuran. Hasil kajian lapangan dan laboratorium menunjukkan bahwa sekitar 52% areal TPSF ini tidak sesuai untuk kelapa sawit karena terdapat faktor pembatas penggunaan lahan yaitu ketebalan gambut >2 meter, tingkat kematangan fibrik, dan lahan ya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The diverse uses of LSNP's plant species include wild animal consumption, human consumption, building materials, medicine, and other applications, with honey production as the most distinguished feature (Table 4). The results align with the conclusion of Sufardi (2015) that swamp woods give both ecological and economic benefits to the community, such as honey producers. In the study area, the use of forest honey is a common community economic activity in the LSNP area, particularly in traditional zones, in an effort to meet traditional community needs (Andryannur et al, 2022).…”
Section: The Use Of the Vegetationssupporting
confidence: 87%
“…The diverse uses of LSNP's plant species include wild animal consumption, human consumption, building materials, medicine, and other applications, with honey production as the most distinguished feature (Table 4). The results align with the conclusion of Sufardi (2015) that swamp woods give both ecological and economic benefits to the community, such as honey producers. In the study area, the use of forest honey is a common community economic activity in the LSNP area, particularly in traditional zones, in an effort to meet traditional community needs (Andryannur et al, 2022).…”
Section: The Use Of the Vegetationssupporting
confidence: 87%
“…This research was a desk study carried out in the Barito watershed in South Kalimantan. Areas that cause flooding downstream are called floodwater discharge areas [14]; [11]; [12]; [14], by overlaying maps such as land system, land cover, and average maximum daily rainfall from CHIRPS (Climate Hazards Group InfraRed Precipitation with Station) from 1990 -2020 at https://www.chc.ucsb.edu/data/chirps. Table 1 shows the maps used in this study area.…”
Section: Methodsmentioning
confidence: 99%
“…The conversion of secondary swamp forests to plantations indicates that land clearing and canalization are taking place [13], especially if the plantation is oil palm. Therefore, changes in land cover from secondary swamp forests to plantations need to be more careful considering the magnitude of the impact of environmental damage that will occur [14].…”
Section: General Characteristics Of the Barito Watershedmentioning
confidence: 99%
“…The establishment of unplanned oil palm plantations is widely acknowledged for its detrimental effects on the crucial functions of these environments, such as carbon storage, hydrological cycles, biodiversity conservation, and the provision of other essential ecosystem services. Despite regulations prohibiting such activities in Aceh, previous research revealed oil palm expansion is continuing in protected areas [11,12]. The lack of effective law enforcement by local authorities has led to rampant illegal logging.…”
Section: Issues and Recommendationsmentioning
confidence: 99%